2009
DOI: 10.1021/ja806062g
|View full text |Cite
|
Sign up to set email alerts
|

Design, Selection, and Characterization of Thioflavin-Based Intercalation Compounds with Metal Chelating Properties for Application in Alzheimer’s Disease

Abstract: Metal chelation is considered a rational therapeutic approach for interdicting Alzheimer's amyloid pathogenesis. At present, enhancing the targeting and efficacy of metal-ion chelating agents through ligand design is a main strategy in the development of the next generation of metal chelators. Inspired by the traditional dye Thioflavin-T, we have designed new multifunctional molecules that contain both amyloid binding and metal chelating properties. In silico techniques have enabled us to identify commercial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
216
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(222 citation statements)
references
References 84 publications
3
216
1
2
Order By: Relevance
“…From these solution speciation diagrams, the concentrations of unchelated Cu 2þ and Zn 2þ (pM ¼ − log½M unchelated ) at a specific pH value can be calculated (pCu ¼ 9.9 and 10.2 at pH 6.6 and pH 7.4, respectively; pZn ¼ 6.1 at pH 7.4). The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37).…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…From these solution speciation diagrams, the concentrations of unchelated Cu 2þ and Zn 2þ (pM ¼ − log½M unchelated ) at a specific pH value can be calculated (pCu ¼ 9.9 and 10.2 at pH 6.6 and pH 7.4, respectively; pZn ¼ 6.1 at pH 7.4). The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37).…”
Section: Resultsmentioning
confidence: 66%
“…The pM values represent the metal binding affinity of L2-b at a specific pH value as well as an estimate of its ability to sequester metal ions bound to Aβ peptide (21,35). The pCu and pZn values for L2-b, corresponding to approximate dissociation constants (K d ), indicated that these K d values were comparable to the reported ones of Cu-Aβ (picomolar to nanomolar) and Zn-Aβ (micromolar) (2,3,8,9,21,(35)(36)(37). Thus, the affinities of L2-b for Cu 2þ and Zn 2þ at the relevant pHs [for metal-induced Aβ aggregation (2-4, 7-9)] suggest that this compound is able to chelate metal ions from soluble Aβ species, which could support the results from reactivity studies of L2-b with metal-treated Aβ species (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of metal-Aβ species in AD pathogenesis, however, has not been clearly elucidated. To advance our understanding of the potential neurotoxicity of metal-Aβ species, efforts to develop chemical tools capable of interacting directly with metal-Aβ species and modulating their reactivity in vitro and in biological systems are under way (1,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In particular, novel bifunctional compounds that contain elements for metal chelation and Aβ interaction have recently been prepared or identified via rational structure-based design strategies or systematic selection of natural products.…”
mentioning
confidence: 99%
“…Indeed, numerous new chelators with potentially better profiles have been developed, including chelators with specific transporters or nanoparticles as chelator carriers, chelators with amyloid-binding activity, and site-activated chelators with antioxidant or anti-acetylcholinesterase (AChE)/monoamine oxidase (MAO) activity (26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%